Involvement in research activities and factors influencing research capacity among dietitians. (12th April 2013) - Howard, A. J.; Ferguson, M.; Wilkinson, P.; Campbell, K. L.
Abstract: Background: A healthcare professional's aptitude to develop research skills and actively engage in research is necessary to optimise healthcare efficacy. The present study investigated the factors that contribute to research capacity within the Australian dietetic workforce. Methods: Queensland‐based dietitians scored their department and individual skill or success in research on a 10‐point scale using an anonymous online survey that incorporated the validated Research Capacity in Context tool. Descriptive statistics were assessed against geographical setting, dietetic experience and the proportion of role (Full Time Equivalent; FTE) designated to research. Research activities were defined by the number of items currently involved in or completed in the past 6 months ( n = 11). Factors associated with research activities were assessed by multivariable linear regression. Results: Dietitians ( n = 130) identified having a moderate skill or success in 14 research items [mean (SD) 5.1 (1.7)] and perceived that their departments provided a moderate level of research support in 19 research items [mean (SD) 6.1 (2.5)]. Geographical setting, the proportion of role designated to research (FTE) and participation in research activities were associated with individual and department ratings of research skill or success. Research involvement was predicted by the proportion of role (FTE) designated to research (β = 0.34, t = 4.16, P < 0.001) and years of experience in dietetics (β = 0.32, t = 2.67, P < 0.009). Conclusions: A dietitian's capacity for research is related to professional experience and the designation of research in the role description. The findings of the present study will provide a baseline of research capacity and expertise among dietitians, and also inform the strategic development of building research capacity.